Discovery of MicroRNAs Associated with the S Type Cytoplasmic Male Sterility in Maize - Jiang-hua YU; Yan-xin ZHAO; Ya-ting QIN; Bing YUE; Yong-lian ZHENG; Hai-lin XIAO (Journal of Integrative Agriculture, 2013)
MicroRNAs (miRNAs) are endogenous small RNAs that play important regulatory roles in the growth and development processes of plants and animals. In this study, we examined the expression profiles of pollen miRNAs from a maize S type cytoplasmic male sterile line and its fertility restored line. In total, 100 known miRNAs belonging to 20 families and 81 novel miRNAs belonging to 44 families were identified. Two and seven known miRNAs had significant expression difference between the two lines at the level of P-value<0.01 and 0.01<P-value<0.05, respectively. Four miRNAs showing >1.5 fold expression difference were verified by stem-loop RT-qPCR. Gene Ontology analysis of miRNA target genes revealed that these genes mainly participated in the transcriptional regulation processes.